MALAYSIAN AMBASSADOR TO INDONESIA HELPS PROMOTE BILATERAL RELATIONS THROUGH EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
JAKARTA, INDONESIA, 29 September 2015 – The Malaysian Ambassador to Indonesia, TYT Dato' Seri Zahrain M. Hashim welcomed the efforts for collaboration between Universiti Sains Malaysia (USM) and various Indonesian partners, in particular the universities in Indonesia.